Intention and Usage of Computer Based Information Systems in Primary Health Center - Hosizah Hosizah; Kuntoro Kuntoro; Hari Basuki (International Journal of Evaluation and Research in Education (IJERE), 2016)
The computer-based information system (CBIS) is adopted by almost all of in health care setting, including the primary health center in East Java Province Indonesia. Some of softwares available were SIMPUS, SIMPUSTRONIK, SIKDA Generik, e-puskesmas, etc. Unfortunately they were most of the primary health center did not successfully implemented. This study applied the Unified Theory of Acceptance and Use of Technology (UTAUT) to assess intention and usage of CBIS in East Java. It was a cross-sectional survey, conducted on February-Maret 2015. A total 30 of user CBIS were identified and questioners were distributed which 100% completed. The user’s CBIS intention was significantly influenced by performance expectancy, effort expectancy and social influence. CBIS usage was significantly influenced by user’s intention and facilitating conditions. UTAUT results indicated that the facilitating conditions have a major impact to use of CBIS in primary health center. The results of this study can be helpful to the East Java provincial Health Office to adjust their program strategies and tactic for providing user’s CBIS facilities in order to implement CBIS successfully.